Pengaruh Kurs, Tingkat Inflasi, Tingkat Bunga dan Jumlah Uang Beredar Terhadap Kemampulabaan Bank Umum di Indonesia Periode Tahun 2006 - 2009 - Rahmiati, Tetty Sari (Business and Management Review, 2011)
Abstract This research is to analize the influence of Rupiahs to US Dollar rate, inflation rate, 1 month central bank certificate, quantity money supply (M1) to general bank net interest margin (NIM) in 2006 – 2009 periods. This research using NIM as a proxy of profitability ratio. Using NIM general bank secondary data from Indonesian Banking Statitistics (SPI), data M1 found from Indonesian Financial Economic Statistical (SEKI) from Central Bank, and then inflation rate found from Central Statistic Bureau (BPS). This research using non probability sampling technique. Descriptive and inferensial statistic was used to test the classical assumption, t test, F test, multiple linear regression, and multiple determination (R2). Research output found that money supplydidn’t significantly influencegeneral bank NIM partially. While Rupiahs to US Dollar rate positively influence general bank NIM, then inflation rate positively influencegeneral bank NIM, Central Bank Certificate interest rate positively influencegeneral bank NIM at 5% α. Rupiahs to US Dollar rate, inflation rate, 1 month Central Bank Certificate interest rate, money supply variables influence 52% to general bank NIM variable. Dominantly Rupiahs to US Dollar rate variable to general bank NIM. For further, this research recommended that another indicator must be taken to increasing the proxy for example Return on asset (ROA), Return of  equity (ROE), Operational Income and Operational Cost (BOPO).   Keywords : Rupiahs to US dollar rate, inflation rate, 1 month central bank certificate, quantity money supply and net interest margin